Epstein-Barr Virus Infection and Thiopurine Therapy in a Pediatric Population with Inflammatory Bowel Disease - Espinheira,Maria Do Céu (2020)
Epstein Barr virus (EBV) primoinfection may contribute to the development of post-mononucleosis lymphomas in EBV-seronegative adult males with inflammatory bowel disease (IBD) under thiopurine therapy, but data on children are sparse. Knowledge of the EBV status may influence the type of surveillance and therapy in a group particularly vulnerable to the occurrence of EBV primoinfection. We aimed to determine the EBV status at diagnosis, the primoinfection rate, and complications in a pediatric Portuguese population with IBD. Method: This was a retrospective analysis of clinical records of pediatric patients with IBD. Demographic data, EBV status, as well as clinical and therapeutic data on primoinfection were collected. Results: Of the 250 patients evaluated, 229 (91.6%) had documented EBV screening and 50.8% were male. Mean age ± SD was 13.0 ± 2.8 years at diagnosis and 14.7 ± 2.3 years at EBV screening. EBV IgG serology was positive in 76.0% of patients. A total of 218 patients had been on therapy with azathioprine at some point. The average length of exposure to azathioprine was 4 years, and 91 patients (39.7%) were on azathioprine at EBV assessment. EBV primoinfection was documented in 4 patients (1.6%), all females, 2 of whom were on azathioprine. Two presented clinical signs of infection and 2 were identified at diagnostic screening; the first 2 suspended azathioprine and the other 2 did not initiate it. Conclusions: A significant proportion of pediatric Portuguese IBD patients are EBV-naïve. Systematic screening of EBV status enables the identification of patients at risk of primoinfection, and the occurrence of symptoms suggestive of acute EBV infection in seronegative patients should lead to rapid confirmation of the diagnosis. Timely diagnosis may allow the adjustment of therapeutic strategy sparing patients from potentially severe iatrogeny.